Michel de Certeau cultural theorist - Buchanan, Ian 1969- (Theory, culture & society)
This volume provides a critical introduction to the work and influence of Michel de Certeau. It discusses his relationship to theories of modern culture and society and ponders how his work would have developed had he not died prematurely